2016
DOI: 10.1038/srep30450
|View full text |Cite
|
Sign up to set email alerts
|

Large area and deep sub-wavelength interference lithography employing odd surface plasmon modes

Abstract: In this paper, large area and deep sub-wavelength interference patterns are realized experimentally by using odd surface plasmon modes in the metal/insulator/metal structure. Theoretical investigation shows that the odd modes possesses much higher transversal wave vector and great inhibition of tangential electric field components, facilitating surface plasmon interference fringes with high resolution and contrast in the measure of electric field intensity. Interference resist patterns with 45 nm (∼λ/8) half-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…[ 110 ] The achievable feature size is about 31 nm at a wavelength of 442 nm, and can be further reduced to 19.5 nm at a wavelength of 363.8 nm. [ 111 ] Quite recently, 32 and 22 nm half‐pitch interference lithography was also realized when the lithography structure was separated from the mask, [ 112 ] so that the mask could be protected and used multiple times. Third, by combining the multilayer hyperbolic metamaterial and metal‐photoresist‐metal configuration, the purities of interference modes are further improved, leading to interference patterns with much better contrast, up to 0.98.…”
Section: Coupled Fields Function For Super‐resolution Imaging and Litmentioning
confidence: 99%
“…[ 110 ] The achievable feature size is about 31 nm at a wavelength of 442 nm, and can be further reduced to 19.5 nm at a wavelength of 363.8 nm. [ 111 ] Quite recently, 32 and 22 nm half‐pitch interference lithography was also realized when the lithography structure was separated from the mask, [ 112 ] so that the mask could be protected and used multiple times. Third, by combining the multilayer hyperbolic metamaterial and metal‐photoresist‐metal configuration, the purities of interference modes are further improved, leading to interference patterns with much better contrast, up to 0.98.…”
Section: Coupled Fields Function For Super‐resolution Imaging and Litmentioning
confidence: 99%
“…Under some special conditions, it has been developed to SPP lithography, which could be possibly generalized for wider applications. For example, Xiangang Luo et al built an SPP lithograph system to realize sub-22-nm half-pitch lithography, providing a viable alternative to traditional costly and complex optical lithography systems [204,205] . Moreover, the innovative concept also illuminates possible applications in other fields, such as photonic chips with signal transmission in subwavelength scales [61] and new platforms revealing novel physics such as photonics Weyl media [63] .…”
Section: Application Scenariosmentioning
confidence: 99%
“…Surface plasmons [13,14] are widely used in many fields because of their advantages of field enhancement and large wave vectors. Surface plasmon interference lithography [15][16][17][18] based on a prism or specially designed mask coupling facilitates the fabrication of subwavelength structures that break through the diffraction limit. Many research results on surface plasmon interference lithography have confirmed the high resolution of the subwavelength structure fabricated by this lithography technology; however, its aspect ratio is low [19].…”
Section: Introductionmentioning
confidence: 99%